Can electromagnetic-navigated maxillary positioning replace occlusional splints in orthognathic surgery?: A clinical pilot study - Berger, Moritz; Nova, Igor; Kallus, Sebastian; Ristow, Oliver; Freudlsperger, Christian; Eisenmann, Urs; Dickhaus, Hartmut; Engel, Michael; Hoffmann, Jürgen; Seeberger, Robin (Journal of cranio-maxillofacial surgery, 2017)
Introduction Because of the inaccuracy of intermaxillary splints in orthognathic surgery, intraoperative guidance via a real time navigation system might represent a suitable method for enhancing the precision of maxillary positioning. Therefore, in this clinical trial, maxillary repositioning after Le Fort I osteotomy was guided splintless by an electromagnetic navigation system. Materials and methods Conservatively planned maxillary reposition in each of 5 patients was transferred to a novel software module of the electromagnetic navigation system. Intraoperatively, after Le Fort I osteotomy, the software guided the maxilla to the targeted position. Accuracy was evaluated by pre- and postoperative cone beam computer tomography imaging (the vectorial distance of the incisal marker points was measured in three dimensions) and compared with that of a splint transposed control group. Results The repositioning of the maxilla guided by the electromagnetic navigation system was intuitive and simple to accomplish. The achieved maxillary position with a deviation of 0.7 mm on average to the planned position was equally accurate compared with that of the splint transposed control group of 0.5 mm (p > 0.05). Discussion The data of this clinical study display good accuracy for splintless electromagnetic-navigated maxillary positioning. Nevertheless, this method does not surpass the splint-encoded gold standard with regard to accuracy. Future investigations will be necessary to show the full potential of electromagnetic navigation in orthognathic surgery.
Gesehen am 03.05.2018